DEVELOPMENT POLICY AND ROADMAP SYARIAH BANKING: KEBIJAKAN PENGEMBANGAN DAN ROADMAP PERBANKAN SYARIAH - Anjani, Vira; Aisyah, Nur; Rizki, Ainur (LPPM UPMI, 2023)
This study discusses the influence between work environment variables and work discipline on employee performance through job satisfaction as an intervening variable (Study at the Medan City Population and Civil Registry Office). This study aims to determine how much, 1) The Effect of Work Environment on Job Satisfaction at the Office of the Population and Civil Registry Office of Medan City; 2) The Effect of Work Discipline on Job Satisfaction at the Office of the Population and Civil Registry Office of Medan City; 3) The Effect of Work Environment on Employee Performance at the Office of the Population and Civil Registry Office of Medan City; 4) The Effect of Work Discipline on Employee Performance at the Office of the Population and Civil Registry of Medan City; 5) The Effect of Job Satisfaction on Employee Performance at the Office of the Population and Civil Registry of Medan City; and 6) The Effect of Work Environment and Work Discipline on Employee Performance through Job Satisfaction at the Office of the Population and Civil Registry of Medan City. The population of this study were all employees of the Office of Population and Civil Registry of Medan City, totaling 313 people and a sample of 40 employees. Data collection techniques using interviews, documentation and questionnaires with a Likert measurement scale. The results showed that work environment has a positive and significant effect on job satisfaction, work discipline has no positive and significant effect on job satisfaction, work environment has no positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, job satisfaction has no positive and significant effect on employee performance, work environment and work discipline through job satisfaction have a significant effect on employee performance